2023
DOI: 10.1007/s12671-023-02187-4
|View full text |Cite
|
Sign up to set email alerts
|

The Compassion Balance: Understanding the Interrelation of Self- and Other-Compassion for Optimal Well-being

Abstract: Objectives This study examined the role of self-other harmony in the relations between self-compassion, other-compassion, and well-being. Past research has shown self- and other-compassion to be positively related. But we hypothesised that self-compassion can be perceived as incompatible with other-compassion, and that self-compassion and other-compassion might be uncorrelated or negatively correlated in daily life for some individuals. We termed this pattern lack of self-other harmony in compass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Also, internet addiction levels had a medium effect size on symptoms of social anxiety for 23% of our study participants, while for 32% the effect was large. These findings may indicate the existence of different profiles of emotional and behavioral dynamics relating internet usage to social anxiety, underscoring the need for a more personalized approach when developing treatment, focusing efforts, and optimizing resources (Hayes et al, 2019(Hayes et al, , 2022Sahdra et al, 2023).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Also, internet addiction levels had a medium effect size on symptoms of social anxiety for 23% of our study participants, while for 32% the effect was large. These findings may indicate the existence of different profiles of emotional and behavioral dynamics relating internet usage to social anxiety, underscoring the need for a more personalized approach when developing treatment, focusing efforts, and optimizing resources (Hayes et al, 2019(Hayes et al, , 2022Sahdra et al, 2023).…”
Section: Discussionmentioning
confidence: 95%
“…By doing this, it is possible to estimate a measure of the overall effect size (fixed effect) and an effect size for each participant based on their individual slopes. Consistently, and in keeping with the recent calls to characterize the heterogeneity of fixed effects, which is often under-reported (e.g., Hayes et al, 2022 ; Ciarrochi et al, 2023 Sahdra et al, 2023 ), we aimed to examine the distribution of the effect size of individual slopes of our effects of interest. The fixed effect sizes do not necessarily characterize the experience of every person in the sample.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Sahdra et al (2024) examined intensive longitudinal data and found that while valued action was associated with higher hedonic well-being (e.g., lower sadness, higher joy) at the group level, there was a subset of people labeled stoics, for whom it was not associated with higher hedonic well-being and indeed was associated with higher stress. In another intensive longitudinal study, Sahdra et al (2023) found that compassion was associated at the group level with higher well-being. However, at the individual level, it was not associated with well-being if the person experienced conflict between self and other compassion.…”
mentioning
confidence: 94%
“…Practitioners often encounter several problems with this recommendation. First, not all components or processes targeted by a protocol are universally applicable to every person (Hayes et al, 2019;Sahdra et al, 2023Sahdra et al, , 2024. This variability is reflected in differing dropout and response rates from standardized protocols (Imel et al, 2013) and in some clients finding a single session satisfactory (Hoyt et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation